The Practice of Excluding Students from Large-scale Assessments: Interviews with Principals - Miller, Tess; FitzGerald, Anne Marie; Xu, Han (Alberta Journal of Educational Research, 2022)
Given the shortage of literature examining exclusion rate practices in Canada, this study reported on exclusion rate practices from principals' perspectives. Specifically, factors influencing principals’ decision-making regarding excluding students from large-scale assessments (LSAs) were explored. We inquired about factors and implications of social promotion as well as decision-making based on compassion, particularly in relation to students who were working below grade level. Using a qualitative research design, we conducted interviews with eight school principals and one vice-principal. Findings revealed an absence of clarity and governance in LSAs that likely influenced differences in principals’ decision-making. Some principals would automatically exclude students who had an Individualized Education Plan, while others would review student files to determine which students to exclude. There was also a discrepancy surrounding which educational supports were permitted on the LSAs. Keywords: Large-scale Assessment, Exclusion Rates, Social Promotion, Principal Leadership, Accountability Étant donné le manque de documentation sur les pratiques en matière de taux d'exclusion au Canada, cette étude porte sur les pratiques en matière de taux d'exclusion du point de vue des directeurs d'école. Plus précisément, nous avons exploré les facteurs qui influencent la prise de décision des directeurs d'école concernant l'exclusion des élèves des évaluations à grande échelle (EGE). Nous nous sommes renseignées sur les facteurs et les implications de la promotion sociale ainsi que sur la prise de décision fondée sur la compassion, en particulier en ce qui concerne les élèves qui travaillent en dessous du niveau scolaire. À l'aide d'un modèle de recherche qualitative, nous avons mené des entretiens avec huit directeurs d'école et un directeur adjoint. Les résultats ont révélé un manque de clarté et de gouvernance dans les EGE, ce qui a probablement influencé les différences dans les décisions des directeurs d'école. Certains directeurs d'école excluaient automatiquement les élèves qui avaient un plan d'enseignement personnalisé, tandis que d'autres examinaient les dossiers des élèves pour déterminer lesquels exclure. Il y avait également une divergence quant aux soutiens éducatifs autorisés dans le contexte des EGE. Mots clés : évaluation à grande échelle, taux d'exclusion, promotion sociale, leadership du directeur d'école, responsabilisation